Hospitalization With Clostridioides difficile in Pediatric Inflammatory Bowel Disease: a Population-Based Study. Issue 2 (7th June 2022) - Kuenzig, M. Ellen; Benchimol, Eric I.; Bernstein, Charles N.; Bitton, Alain; Carroll, Matthew W.; Griffiths, Anne M.; Kaplan, Gilaad G.; Nguyen, Geoffrey C.; Otley, Anthony R.; Stukel, Therese A.; Dummer, Trevor J.B.; El-Matary, Wael; et al.
Abstract : Objectives: Several studies have demonstrated higher rates of Clostridioides difficile infection (CDI) in adults with inflammatory bowel disease (IBD). We conducted a population-based study comparing the risk of hospitalization with CDI in children with and without IBD. Methods: Using health administrative data and validated algorithms, we identified all children (<16 years) diagnosed with IBD in 5 Canadian provinces, then age and sex matched to 5 children without IBD. Province-specific 5-year incidence rates of hospitalization with CDI were pooled and generalized linear mixed-effects models were used to estimate the crude incidence rate ratio (IRR) comparing (1) children with and without IBD and (2) children with Crohn disease and ulcerative colitis. Hazard ratios (HR) from Cox proportional hazards models adjusting for age, sex, rural/urban household, and income were pooled using fixed-effects models. Results: The incidence rate of CDI identified during hospitalization was 49.06 [95% confidence interval (CI), 39.40–61.08] per 10, 000 person-years (PY) in 3593 children with IBD compared to 0.39 (95% CI, 0.13–1.21) per 10, 000 PY in 16, 284 children without IBD (crude IRR, 133.4, 95% CI, 42.1–422.7; adjusted HR, 68.2, 95% CI, 24.4–190.4). CDI was identified less often in children with Crohn disease than ulcerative colitis (crude IRR, 0.51, 95% CI, 0.32–0.82; adjusted HR, 0.69, 95% CI, 0.46–1.05). Conclusions: Children with IBD have a markedly higher incidence of CDI identified during a hospitalization relative to children without IBD. Consequently, symptomatic children with IBD who are hospitalized should be screened for CDI.